S* -SEPARATION AXIOMS - Mahmood, Sabiha; Ibraheem, Afrah (Iraqi Journal of Science, 2024)
In this paper we introduce a new type of separation axioms which we calls*-separation axioms. We obtain the definition from standard separationproperties by replacing open set by s*-open set in their definitions.Moreover, we study the relation between this type of separation axioms andeach of generalized separation axioms (g-separation axioms) and standardseparation axioms.